(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: A few studies of Bangladeshi children have reported an independent association between severe zinc deficiency and acute lower respiratory tract infection (ALRTI) after adjusting for important confounders, although evidence to the contrary also exists. The current study was conducted to examine the relationship between low zinc levels in children with ALRTI and in those without respiratory disease who attended a tertiary hospital in Bangladesh. Methods: This hospital-based case-control study was conducted among 36 children aged 2–60 months with ALRTI and 36 controls without respiratory illness. Clinical data were recorded, and serum zinc levels were measured within 24 hours of enrollment. Multivariate logistic regression was used to adjust for age, sex, family size, maternal education, breastfeeding, immunisation status, passive smoking exposure and anthropometric indices. Results: The median (inter-quartile range) serum zinc level was significantly lower among cases than controls [82.5 (51.5–102.3) µg/dL vs. 133.0 (100.8–171.0) µg/dL; P < 0.001]. Zinc deficiency (serum zinc ≤60 µg/dL) was more frequent among cases (41.7%) than controls (2.8%). After adjustment for age, sex, family size, breastfeeding, anthropometric indices, immunisation, maternal education, and passive smoking exposure, low serum zinc levels were independently associated with ALRTI (adjusted OR = 26.2; 95% CI: 2.8–248.6). Passive smoking exposure was also independently associated with ALRTI (adjusted OR = 5.6; 95% CI: 1.5–21.0). Conclusion: Low serum zinc levels (≤60 µg/dL) were strongly associated with ALRTI among children, with affected children having approximately 26-fold higher odds of ALRTI than those with higher zinc levels. These findings suggest that zinc deficiency may be an important modifiable risk factor for ALRTI in this population.